Decision Support System for Selecting University in Pekanbaru Based on Android - Dewi Nasien; M. Hasmil Adiya; Mulyadi, Ahmad; Sukabul, Ahmad; Rianda, Gilang; Yulianti, Deni (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2020)
Nowadays development of technology is growing fast, especially Android Operating System (OS). Android is a technology that can help human to improve their works both quality and quantity, e.g. making decisions. This study discusses the application of decision support systems to select university. Many students are still confused to select the best university for them. Hence, this application aims to assist students for making decisions using weighted product (WP) method. It exploits some criteria namely, distance, university accreditation and number of lecturers. The research methodology are used namely problem analysis, analysis both hardware and software requirements, design system, implementation and testing. Ultimately, application can be utilized. This application is built on Android Studio and Java Development Kit. It is implemented in Universities in Riau. This application can help students to choose the best university quickly and accurately.